2004
DOI: 10.1111/j.0022-202x.2004.23411.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Variation in the Erythemal Response to Ultraviolet Radiation and Photoadaptation

Abstract: We have studied the cutaneous response to ultraviolet radiation, measured objectively as erythema in a sample of 12 body sites on 15 Northern European subjects with multiple doses of ultraviolet B (UVB). Skin pigmentation and the development of photoadaptation in response to five repeated doses of irradiation at three body sites was also measured. We report striking differences of up to 5-fold at different body sites to the same challenge dose (p < 0.001) and demonstrate that for this population, site variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 21 publications
0
44
1
Order By: Relevance
“…On two previously marked adjacent sites, we evenly applied by means of a rubber glove 2 mg/cm 2 tacrolimus ointment and 2 mg/cm 2 vehicle thrice daily over a 3-day period (9 applications in total). In order to minimize anatomically dependent variations of UV sensitivity, the interventions and measurements were carried out at the same horizontal level (medial scapular region) [14]. All test substances were administered in a non-blinded manner according to a fixed plan.…”
Section: Uv Irradiation Protocol and Application Of Test Substancesmentioning
confidence: 99%
“…On two previously marked adjacent sites, we evenly applied by means of a rubber glove 2 mg/cm 2 tacrolimus ointment and 2 mg/cm 2 vehicle thrice daily over a 3-day period (9 applications in total). In order to minimize anatomically dependent variations of UV sensitivity, the interventions and measurements were carried out at the same horizontal level (medial scapular region) [14]. All test substances were administered in a non-blinded manner according to a fixed plan.…”
Section: Uv Irradiation Protocol and Application Of Test Substancesmentioning
confidence: 99%
“…To the Editor: Waterston et al (2004) have confirmed that there is marked variability between body sites in ultraviolet-induced erythemal responses. Although there are differences in erythemal responses to different ultraviolet wavebands (Olson et al, 1966), their findings are in line with those of the earlier studies in which unfiltered mercury arc lamps (Schall and Alius, 1926;Wucherpfennig, 1931) and a xenon arc monochromator delivering different wavebands (Olson et al, 1966) were used.…”
mentioning
confidence: 91%
“…The primary purpose of pre-treatment MED testing is to determine a starting dose that will not cause uncomfortable (or more serious) erythema. Waterston et al (2004) found (as shown in their Fig 3) that if a whole-body starting dose of 50% MED (upper back, 24 h reading) was selected for their 15 study volunteers not one would have received a dose greater than the MED on any tested body site. If a 70% upper-back MED starting dose was used only four subjects would have received a dose slightly above the MED on the chest or lower back.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In this issue of the journal, Waterston et al (2004) studied the cutaneous response to ultraviolet B (UVB) radiation in normal human subjects of Fitzpatrick phototypes I and II by first measuring erythema responses at multiple anatomical sites. They administered a series of incremental doses of energy between 38 and 300 mJ per cm 2 at 12 pairs of body sites.…”
mentioning
confidence: 99%